2015
DOI: 10.1007/s11605-015-2856-6
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach to Medical Weight Loss Prior to Complex Abdominal Wall Reconstruction: Is it Feasible?

Abstract: Obesity is a major risk factor for perioperative morbidity, especially for patients undergoing complex incisional hernia repair. The feasibility and effectiveness of medical weight loss programs prior to complex abdominal wall reconstruction have not been well characterized. Here, we report our experience collaborating with a medical weight loss specialist utilizing a protein sparing modified fast in order to optimize weight loss prior to complex abdominal wall reconstruction. Morbidly obese patients (body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 28 publications
0
52
1
2
Order By: Relevance
“…A recent study demonstrated that medically supervised weight loss prior to AWR can significantly reduce postoperative complications among morbidly obese patients and it can be considered a possible additional strategy to minimize SSO. [7] In contrast, non-surgical weight loss before AWR can lead to a delay of the AWR procedure. [7, 39] Nonetheless, the effects of preoperative weight loss on AWR outcomes, particularly hernia recurrence, are still not clear, and further research on this topic is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study demonstrated that medically supervised weight loss prior to AWR can significantly reduce postoperative complications among morbidly obese patients and it can be considered a possible additional strategy to minimize SSO. [7] In contrast, non-surgical weight loss before AWR can lead to a delay of the AWR procedure. [7, 39] Nonetheless, the effects of preoperative weight loss on AWR outcomes, particularly hernia recurrence, are still not clear, and further research on this topic is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…[7] In contrast, non-surgical weight loss before AWR can lead to a delay of the AWR procedure. [7, 39] Nonetheless, the effects of preoperative weight loss on AWR outcomes, particularly hernia recurrence, are still not clear, and further research on this topic is warranted. [39]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations